Wolbachia and cytoplasmic incompatibility in mosquitoes. - Sinkins, S (2004)
Wolbachia are maternally inherited bacteria that induce cytoplasmic incompatibility in mosquitoes, and are able to use these patterns of sterility to spread themselves through populations. For this reason they have been proposed as a gene drive system for mosquito genetic replacement, as well as for the reduction of population size or for modulating population age structure in order to reduce disease transmission. Here, recent progress in the study of mosquito Wolbachia is reviewed. We now have much more comprehensive estimates of the parameters that can affect the spread of Wolbachia through natural populations from low starting frequencies, and for waves of spread to be maintained in the face of partial barriers to gene flow. In Aedes albopictus these dynamics are extremely favourable, with very high maternal transmission fidelity and levels of incompatibility recorded. Correspondence between measurements taken in the lab and field is much better than in the Drosophila simulans model system. Important research goals are also discussed, including Wolbachia transformation, interspecific transfer and the elucidation of the mechanisms of incompatibility and rescue; all will be aided by a wealth of new Wolbachia genome information.